Effects of biological maturity on hydration status and sweat responses to match play in highly-trained young soccer players - Gurr, S.; Al Haddad, H.; Mendez-Villanueva, J. A. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Introduction Empirical field based data on the hydration status and sweat response of highly trained young soccer players during competitive matches is scarce (Da Silva et. al., 2012). Laboratory based studies that have examined the thermoregulatory response in children and adolescents during continuous exercise modes have found post-pubertal children sweat more than pre-pubertal children when exercising at the same relative intensity (Araki et. al., 1979; Falk et. al., 1992). However, it is not clear whether the results of these studies are readily applicable to the intermittent nature of soccer played outdoors. The aim of this study was to compare the pre-match hydration status and sweat response of highly-trained adolescent soccer players differing in biological maturity during competitive soccer matches played in warm conditions. Methods: Thirty nine players (Age: 14.7 ± 1.4 yrs; body mass: 49.1 ± 9.2 kg: Height: 165.4 ± 8.9 cm) from the same football academy were monitored for hydration status and sweat response during eleven games lasting 70-90 minutes. Urine samples were collected before the game and analyzed for osmolality. Sweat loss was assessed from the change in body mass after correction for fluid intake and urine losses. Heat Index (HI) was used as a marker of environmental conditions. Players were later subdivided into three non-overlapped maturational groups based on their age of predicted height velocity (APHV):1) Pre-APHV <-1.1 yrs to PHV (n=11), around the estimated APHV (Circum-APHV >-1yrs to PHV to <+1 yrs) (n=18) and post-APHV (>1 PHV) (n=10). Differences in the mean values were assessed using a one-way ANOVA. Bonferroni`s post hoc tests was applied when a significant interaction was found. Results: There was no significant difference in the environmental conditions (HI-33.2 ± 2.5°C pre-APHV; 35.2 ± 3.7°C circum-APHV; 34.6 ± 1.9°C post-APHV; p=0.25) or in the pre-match hydration status (699 ± 311 mOsm/kg pre-APHV; 884 ± 217 mOsm/kg circum-APHV; 673 ± 377 mOsm/kg post-APHV; p=0.12) between the groups. There were significant differences between all groups for percentage change in body mass (Pre-APHV vs. Post-APHV (0.8 ± 0.6 vs. 2.3 ± 0.8; p <0.001); Circum-APHV vs. Post-APHV (1.5 ± 0.7 vs. 2.3 ± 0.8; p =0.022); Pre-APHV vs. Circum-APHV (0.8 ± 0.6 vs 1.5 ± 0.7;p=0.045). Corrected for differences in body mass, a significant difference in sweat losses was only observed between Pre-APHV and Post-APHV groups (19.6 ± 4.4 vs. 25.9 ± 4.5 ml/kg/hr; p= 0.017). Discussion: This study supports previous laboratory-based findings that pre-pubertal adolescents rely less on evaporative sweat loss than post-pubertal adolescents when exercising in the heat. The large variability sweat rates within groups reinforces the need to individualise hydration advise for players.